Price determinants of newly built dwellings in Serbia - Nikolic, Ivan (Industrija, 2015)
This paper analyses the determinants of newly built dwelling prices in Serbia in a panel of 24 cities over the period 2011-2014. Results suggest that dwelling prices primarily tend to rise with population growth and real total net wages as a proxy of household incomes, while declines in effective interest rate on housing loans are associated with higher dwelling prices. Additional explanatory variables, such as the level of development of observed cities, geographical distance from the capital, or real GDP dynamics in the country, despite the expected correlation, didn’t have a statistically significant influence on the dependant variable.